The wider context of performance analysis and it application in the football coaching process - Wright, C.; Carling, C.; Collins, D. (International Journal of Performance Analysis in Sport, 2014)
The evolving role of PA and the associated proliferation of positions and internships within high performance sport has driven consideration for a change, or at least a broadening, of emphasis for use of PA analysis. In order to explore the evolution of PA from both an academic and practitioner perspective this paper considers the wider conceptual use of PA analysis. In establishing this, the paper has 4 key aims: (1) To establish working definitions of PA and where it sits within the contemporary sports science and coaching process continuum; (2) To consider how PA is currently used in relation to data generation; (3) To explore how PA could be used to ensure transfer of information, and; (4) To give consideration to the practical constrains potentially faced by coach and analyst when implementing PA strategies in the future.